Analisis Manajemen Laboratorium Biologi SMA Negeri di Kabupaten Batanghari Provinsi Jambi: Analysis of Biology Laboratory Management of Senior High School in Batanghari Regency, Jambi Province - Tiara Balqis; Afreni Hamidah; Mia Aina (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2018)
Laboratory is a facility to support the activities of learning in school, every high school should has a good laboratory management to support biology learning activities. This study aimed to analyze the biology laboratory management that has been done by the senior high school laboratory manager in the district of Batanghari in Jambi province. The research is descriptive study; the research subjects are research laboratory heads and teachers of biology. The laboratory management analysis includes aspects of planning, organizing, structuring, administering, and securing. In this study the data obtained from observation, questionnaire, interview, and documentation. The obtained data were analyzed descriptively. Overall, two schools are categorized as excellence (SMAN A; 89.2 % and SMAN B; 87.9%); two schools are in very good category (SMAN C; 78.2% and SMAN D; 78.0%); and two schools are in the last category (enough category) includes SMAN E (66.8%) and SMAN F (61.5%). Moreover some aspect of biology laboratory management in senior high schools are not well managed yet. Based on the results it is suggested that laboratory managers should improve the laboratory facilities as well as their competencies in managing the laboratory. Moreover, senior high schools should employ laboratory technicians and laboran to assist the task of laboratory heads and teachers to produce a more effective laboratory management